2016
DOI: 10.1128/mcb.00054-16
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Ago2 and Subsequent Inactivation of let-7a RNP-Specific MicroRNAs Control Differentiation of Mammalian Sympathetic Neurons

Abstract: MicroRNAs (miRNAs) are small regulatory RNAs that regulate gene expression posttranscriptionally by base pairing to the target mRNAs in animal cells. KRas, an oncogene known to be repressed by let-7a miRNAs, is expressed and needed for the differentiation of mammalian sympathetic neurons and PC12 cells. We documented a loss of let-7a activity during this differentiation process without any significant change in the cellular level of let-7a miRNA. However, the level of Ago2, an essential component that is assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 42 publications
4
31
0
Order By: Relevance
“…In a previous report, we delineated how p38 activation is linked with miRNP inactivation, which causes the differentiation of mammalian cells (25). Here, we also observed how the activation of the p38 pathway is ensured by P-body components and how it may be linked with the prevention of apoptosis that is possibly caused by the reactivation of miRNPs in NGF-depleted cells.…”
Section: Increased Expression Of P-body Components Reverses the Mirnasupporting
confidence: 59%
See 1 more Smart Citation
“…In a previous report, we delineated how p38 activation is linked with miRNP inactivation, which causes the differentiation of mammalian cells (25). Here, we also observed how the activation of the p38 pathway is ensured by P-body components and how it may be linked with the prevention of apoptosis that is possibly caused by the reactivation of miRNPs in NGF-depleted cells.…”
Section: Increased Expression Of P-body Components Reverses the Mirnasupporting
confidence: 59%
“…Here, we also observed how the activation of the p38 pathway is ensured by P-body components and how it may be linked with the prevention of apoptosis that is possibly caused by the reactivation of miRNPs in NGF-depleted cells. As let-7a inactivation is known to be essential in the NGF-induced differentiation process (25), we studied the connection between let-7a activity and NGF withdrawal. Let-7a activity was observed to increase with increasing time periods of NGF withdrawal from differentiated PC12 cells (Fig.…”
Section: Increased Expression Of P-body Components Reverses the Mirnamentioning
confidence: 99%
“…We noted an increased association of PP2A with the endosome enriched fraction in Ld ‐infected cells (Fig N). It is important to note that substrate of PP2A, the phosphorylated Ago2, is also known to get concentrated in these fractions as we had analysed them before both in macrophage and neuronal cells [Fig L and M (Mazumder et al , ; Patranabis & Bhattacharyya, )]. Therefore, PP2A may act on its substrate phosphorylated Ago2 in the Optiprep density gradient fractions 2–4 that are positive for MVB marker protein Alix.…”
Section: Resultsmentioning
confidence: 95%
“…miRNA-mediated regulation controls varieties of genes including several cytokine encoding genes (Palanisamy et al, 2012). It has also been observed that reversible uncoupling of miRNA from Ago2 ensures switching of miRNA activity in mammalian cells (Mazumder et al, 2013;Patranabis & Bhattacharyya, 2016). It has also been noted that Ld infection controls expression of several miRNAs including those that act as repressor of pro-inflammatory cytokine mRNAs (Chakrabarty & Bhattacharyya, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…(5) Regulation of the composition and activity of the neuronal miRISC. This includes the activity-dependent control of the phosphorylation of Ago2 (Patranabis and Bhattacharyya, 2016) or its interacting partner FMRP (also known as FMR1) (Muddashetty et al, 2011), as well as the activity-regulated degradation of the miRISC protein MOV10 (Banerjee et al, 2009). such miRNA therapeutics might also prove to be applicable to neurodevelopmental disorders for which no cure is currently available.…”
Section: Discussionmentioning
confidence: 99%